Correlation of Vitamin D Levels with the Severity of Atopic Dermatitis Among Filipino Children Aged 1 Month to 18 Years Old Using the SCORAD Index - Reyes, Roche Dana; Recto, Marysia Stella; Castor, Mary Anne; Casis Hao, Roxanne; Sumpaico, Madeleine (Philippine Journal of Allergy, Asthma and Immunology, 2024)
Objective: To correlate Vitamin D levels with the severity of atopic dermatitis (AD) using the SCORAD index. Methodology: Patients aged 1 month to 18 years seen at the Philippine General Hospital Outpatient Department, diagnosed with AD based on Hanifin and Rajka criteria, were recruited into the study. The extent and severity of AD were assessed using the SCORAD index. Serum concentrations of vitamin D were determined using the Beckman Coulter Radioimmunoassay, California. Results: A total of 53 patients were included in the study. Mild AD was diagnosed in 27 (50.9%) children, moderate in 21 (39.6%), and severe in 5 (9.4%). Vitamin D insufficiency was observed in 39 individuals (73.6%). Of these, 20 (51.3%) had mild AD, 15 (38.5%) had moderate, and 4 (10.3%) had severe AD. Of the 14 individuals (26.4%) with sufficient vitamin D levels, 7 (50.0%) had mild AD, 6 (42.9%) moderate, and 1 (7.1%) severe. There is no significant correlation between serum vitamin D levels and the actual SCORAD index with a p of 0.26. Conclusion: In conclusion, serum vitamin D level has no significant correlation with the severity of AD as measured by the SCORAD index.